Habitat partitioning in native Geranium species through reproductive interference. (4th January 2020) - Nishida, Sachiko; Takakura, Koh-Ichi; Naiki, Akiyo; Nishida, Takayoshi
Abstract: Background and Aims: Heterospecific pollen transfer may reduce the fitness of recipient species, a phenomenon known as reproductive interference. A theoretical study has predicted that distributions of species pairs affected by reproductive interference may be syntopic under negligible reproductive interference, sympatric but with partitioning at small spatial scale (i.e. allotopic) under weak interference, or exclusive when reproductive interference is strong. Verifying these predictions is essential for evaluation of the applicability of reproductive interference as a general assembly rule of biological communities. The aim of this study was to test these predictions in two sympatrically distributed wild Geranium species, G. thunbergii and G. wilfordii . Methods: To measure the effect of reproductive interference, the associations between the relative abundance of the counterpart species and seed set in the focal species, and seed set reduction following mixed pollination, were analysed. The possibility of hybridization with viable offspring was examined by genotyping plants in the field and after mixed pollination. Fertility of putative hybrids was based on their seed set and the proportion of pollen grains with apertural protrusions. A transect study was conducted to examine spatial partitioning, and possible influences of environmental conditions (canopy openness and soil moisture content) on partitioning between the species were analysed. Key Results: Neither abundance of the counterpart species nor heterospecific pollen deposition significantly affected seed set in the focal species, and hybridization between species was almost symmetrical. Putative hybrids had low fertility. The two species were exclusively distributed at small scale, although environmental conditions were not significantly different between them. Conclusions: The allotopy of the two species may be maintained by relatively weak reproductive interference through bidirectional hybridization. Re-evaluation of hybridization may allow ongoing or past reproductive interference to be recognized and provide insight into the distributional relationships between the interacting plants.